The Clinical Value of the Faux Pas Test for Diagnosing Behavioral-Variant Frontotemporal Dementia. (January 2022) - Delbeuck, Xavier; Pollet, Marianne; Pasquier, Florence; Bombois, Stéphanie; Moroni, Christine
Objective: We studied the clinical value of the faux pas test to diagnose behavioral-variant frontotemporal dementia. Methods: The faux pas test was administered to patients referred to a memory clinic in a context of behavioral disturbances. The diagnosis of behavioral-variant frontotemporal dementia (n = 14) or not (n = 25) was confirmed after a 3 years follow-up. Results: The faux pas test displayed a high sensitivity for behavioral-variant frontotemporal dementia (.83) however its specificity was only moderate (.64). Conclusions: Our results confirm that the FPT capture's specific cognitive impairments in patients with behavioral-variant frontotemporal dementia. However, some patients with psychiatric disease or other neurological diseases may also show impaired scores.